Stress for success - Loehr, James E. (Times Books New YorkUS, 1997)
Attempts to debunk myths about stress and to promote it as the most powerful stimulus to personal growth. Provides tools for assessing personal toughness and explains the central position of the emotions. Details three performer skills that empower individuals to achieve their Ideal Performance State (IPS) on demand. Identifies four specific life skills that expand stress capacity and increase one's sense of harmony.